KEANEKARAGAMAN JENIS ROTAN (Calamus Spp.) DI KAWASAN HUTAN LINDUNG WILAYAH KECAMATAN DAMPELAS SOJOL KABUPATEN DONGGALA - Kunut, Agus A.; Sudhartono, Arief; Toknok, Bau (Jurnal Warta Rimba, 2014)
Rattan is persevering climbing plant and almost can grow in all areas. Rattan is one of forest plant and have commercial price at market. At the public this plant can grow naturally, spread begin from the beach until the mountain and grow fast and relative easy to harvest and transport. Rattan stick can reach for the hundreds meter. Spray water if we slash the stick and can be used for survival at the forest. This research purpose to know many types of rattan at the protection forest area in Dampelas Sojol subdistrict Donggala regency. This research using the box line method with cut contour line. Supervision form with long track 100 m and wide 20 m. furthermore build 20 sub box with format 10 X 10 meter. Number of supervision is 3 track with box placement and intentional directed according â€œpurposive samplingâ€ basic on the area can grow rattan . Research result indicate that kind variety of rattan in Dampelas Sojol subdistrict Donggala regency main kind variety of rattan cacing (Calamus melanoloma Mart) lambang (Calamus ornatus), tohiti (Calamus inops), batang (Calamus zollingeri Becc) and noko (Calamus koordersianus Becc),. The kind of rattan was so dominate is worm rattan with INP 76,67 %. Index kind variety of rattan at the protection forest area in Dampelas Sojol subdistrict Donggala regency include very low with Hâ€™ number 0,52 %. Key word: rattan, protection forest, Donggala.